2005
DOI: 10.1016/j.neuron.2005.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids Control the Induction of Cerebellar LTD

Abstract: The long-term depression (LTD) of parallel fiber (PF) synapses onto Purkinje cells plays a central role in motor learning. Endocannabinoid release and LTD induction both depend upon activation of the metabotropic glutamate receptor mGluR1, require postsynaptic calcium increases, are synapse specific, and have a similar dependence on the associative activation of PF and climbing fiber synapses. These similarities suggest that endocannabinoid release could account for many features of cerebellar LTD. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
275
5
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(296 citation statements)
references
References 86 publications
(182 reference statements)
13
275
5
3
Order By: Relevance
“…1). Safo and Regehr [36] reported that the effects of WIN55212-2 on PF to PN synaptic transmission was fully reversible upon application of AM251, while we found that AM251 (at a concentration effective to block the effect of WIN55212-2) did not reverse the WIN55212-2-induced depression of PF calcium transients. The reason for this discrepancy is unclear.…”
Section: Demonstration Of Preltdcontrasting
confidence: 65%
See 2 more Smart Citations
“…1). Safo and Regehr [36] reported that the effects of WIN55212-2 on PF to PN synaptic transmission was fully reversible upon application of AM251, while we found that AM251 (at a concentration effective to block the effect of WIN55212-2) did not reverse the WIN55212-2-induced depression of PF calcium transients. The reason for this discrepancy is unclear.…”
Section: Demonstration Of Preltdcontrasting
confidence: 65%
“…It has been reported that production of endocannabinoids in PNs is required for cerebellar PF-PN postsynaptic LTD [36]. We examined whether CB1 receptors are involved in preLTD.…”
Section: Hz Stimulation Induced a Cb1 Receptor-dependent Ltd At Pf-pnmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has recently been shown that concurrent parallel fiber/climbing fiber activation of Purkinje cells (which is analogous to convergent CS-US input) leads to short-term depression of the parallel fiber synapse, an effect which is mediated by endocannabinoids (Brenowitz and Regehr, 2005). Such an effect may be crucial for the induction of longer-lasting synaptic plasticity, such as endocannabinoid-mediated long-term depression (LTD; Safo and Regehr, 2005), which itself may represent the neural substrate of EBC (Thompson and Kim, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…CB1Rs are located on the glutamatergic terminals of parallel fibers and the GABAergic terminals of stellate cells and basket cells, and thereby modulate inhibitory and excitatory synaptic transmission to Purkinje cells (Iversen 2003). Activation of CB1Rs is necessary for Purkinje cell LTD (Safo and Regehr 2005). Moreover, Purkinje cell LTD is dependent on release of the endocannabinoid 2-arachidonyl glycerol (2-AG) from Purkinje cells (Safo and Regehr 2005), which results in decreased glutamate release from parallel fibers (Kreitzer and Regehr 2001a,b).…”
mentioning
confidence: 99%